(3eLehY aj GdcjejGAs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3gPG YGaGc Gddg GdHGH GdCUZQ GdPi VefGg Yf GdadGSaI HGH GdMQR dCfg dGjecf GdYGed Cf jNWi ajg hdh GLJgO hgh HGH GdefMg s
(3BNQgG (B:s
(3Ke LFfG HYO Pdc CHhGH bQjHI GdJOGHjQ eGdG Jcai CUHGZgG HCfaSgG Je cJGH GdeLQOGJ GdCcHQ hGddg GdMeO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHY YTQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs